2020
DOI: 10.1038/s41598-020-78641-3
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex specific target of blood pressure for the prevention of cardiovascular event among the treatment naive hypertensive patients

Abstract: The time at which hypertension treatment should be initiated for different age groups and sexes remains controversial. We aimed to determine whether the association between blood pressure (BP) and major adverse cardiovascular events (MACE) varies with age and sex. This study enrolled 327,328 subjects who had not taken antihypertensive medication in the Korean National Health Service-National Health Screening Cohort between 2002 and 2003. Participants were categorized into four groups according to 2017 American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…This discrepancy might be caused by differences in patient characteristics, statistical methods, or whether the use of antihypertensive medication was considered. Interestingly, previous large cohort studies have reported that the relationships between BP and several CVD outcomes were robust in young adults and tended to attenuate with increasing age [ 1 , 36 , 38 ]. Therefore, because CKD and CVD share common risk factors, the age-specific risk of CKD might be similar to the risk of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy might be caused by differences in patient characteristics, statistical methods, or whether the use of antihypertensive medication was considered. Interestingly, previous large cohort studies have reported that the relationships between BP and several CVD outcomes were robust in young adults and tended to attenuate with increasing age [ 1 , 36 , 38 ]. Therefore, because CKD and CVD share common risk factors, the age-specific risk of CKD might be similar to the risk of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…It was indicated that managing heart rate at 65–79 bpm may be beneficial in reducing the risk of MACEs in hypertensive cases, particularly in males and the elderly. The gender and age of hypertensive patients have offered prognostic values for cardiovascular diseases ( 32 , 33 ). Continuous monitoring and management of heart rate may potentially improve the outcomes of hypertensive patients, especially in male and elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that estrogen affects the cardiovascular system, including inducing vasodilation, inhibiting vascular remodeling, regulating reninangiotensin-aldosterone system, and sympathetic nervous system. However, these protective effects can be significantly reversed in postmenopausal women (9). The mean age of hypertensive patients in this study was 64.46±10.65 years old, and the female patients at this age were lacking estrogen.…”
Section: Discussionmentioning
confidence: 56%
“…The disappearance of estrogen’s protective effect in postmenopausal elderly women, which is closely related to increases in blood pressure variability, nocturnal blood pressure load, and cardiovascular events, is likely not related to MACE decreases in hypertensive patients with HR of 70–74 bpm. In addition, previous studies have suggested that elderly age is closely related to the occurrence of MACE, especially in patients with stage 2 hypertension, and the increased risk of MACE was only observed in ≥70 years old patients ( 10 ). The study showed that the relative risk of MACE was lower when HR was 70–74 bpm in hypertensive patients ≥65 years.…”
Section: Discussionmentioning
confidence: 97%